A Systematic Review of the Prevalence of Refractive Errors, Uncorrected Refractive Errors, and Presbyopia in Adults in India (International Journal of Food and Nutritional Sciences, 2022)
Estimating the prevalence of refractive errors, uncorrected refractive error (URE), and uncorrected presbyopia in adults in India under the age of 30 is the goal of this review. Methods: The standards set forth by Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) were adhered to. Using the Cochrane Library, Medline, and Embase, a thorough literature search was conducted to cover all studies published from India starting in the year 1990. Ametropia >0.50 D was used to characterise refractive error. Uncorrected presbyopia is described as near vision N8 improving with correction in the absence of distant URE, while URE is defined as presenting visual acuity (PVA) poorer than 6/18 improving with pinhole or spectacle correction.There were 15 studies from South India, 1 each from Western and Central India, and 1 study that comprised 15 states in total. The prevalence of myopia and hyperopia was 27.7% and 22.9%, respectively, while RE of at least 0.50 D of spherical equivalent ametropia was 53.1% [(95% confidence interval (CI): 37.2-68.5). The prevalence of URE was 10.2% (95% CI: 6.9-14.8), but there was a significant amount of variation. Presbyopia prevalence was 33% (95% confidence interval [CI]: 19.1-51.0). The severity of refractive errors among adults in India is highlighted in this review. In areas where there is a dearth of knowledge on UREs, more investigations utilising conventional techniques are required. Adult eyewear delivery programmes in India must concentrate primarily on reading glasses to treat presbyopia as well as eyewear to treat hyperopia and myopia.